Sosialisasi Pengukuran Body Mass Index Sebagai Pendukung Terbentuknya Berat Badan Ideal Pada Kelompok Kerja Guru - Prastiwi, Bertika Kusuma; Ratimiasih, Yulia (Universitas PGRI Semarang, 2025)
Community service activities aim to provide awareness and understanding of ideal body weight as a preventive measure in health. The main target of this activity is elementary school teachers, in the Batursari Mranggen Teacher Working Group (KKG) as many as 15 teachers, assisted by a team of PPG UPGRIS students. The method used in the community service is PAR (participatory action research). The stages of the activity, observation and analysis of conditions, mapping needs, finding and planning problem solving, implementing the KKG problem solving program regarding ideal body weight. The materials provided are healthy lifestyles, measuring weight and height, calculating BMI. Practical activities are carried out by carrying out weight measurements using a scale. Measuring height and weight comparing the measurement results, calculating with the BMI formula with the BMI standard benchmark, overweight or obesity, underweight, and ideal. The results of the community service are able to create awareness of the importance of ideal body weight for health preventive efforts, with a 75% success rate implemented for oneself and students. Socialization is expected to increase awareness about ideal body weight.